2021
DOI: 10.3390/ijms22189798
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Interactions with Voltage-Gated Sodium Channels

Abstract: Calmodulin (CaM) is a small protein that acts as a ubiquitous signal transducer and regulates neuronal plasticity, muscle contraction, and immune response. It interacts with ion channels and plays regulatory roles in cellular electrophysiology. CaM modulates the voltage-gated sodium channel gating process, alters sodium current density, and regulates sodium channel protein trafficking and expression. Many mutations in the CaM-binding IQ domain give rise to diseases including epilepsy, autism, and arrhythmias b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…The associated structural transition to an open conformation upon Ca 2+ binding mediates interaction with CaM’s targets and signal transduction ( 20 , 21 ). In cardiomyocytes, CaM modulates the activity of several ion channels such as the L-type voltage-gated Ca 2+ channel (Ca v 1.2), voltage-gated Na + channel (Na v 1.5), voltage-gated K + channel (K v 7.1), and ryanodine receptor (RyR2) ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ). Modulation is achieved either via direct binding or through the regulatory multifunctional Ca 2+ /CaM-dependent kinase (CaMKII) with the γ (CaMKIIγ) and δ (CaMKIIδ) isoforms present in heart ( 46 , 47 , 48 , 49 ).…”
mentioning
confidence: 99%
“…The associated structural transition to an open conformation upon Ca 2+ binding mediates interaction with CaM’s targets and signal transduction ( 20 , 21 ). In cardiomyocytes, CaM modulates the activity of several ion channels such as the L-type voltage-gated Ca 2+ channel (Ca v 1.2), voltage-gated Na + channel (Na v 1.5), voltage-gated K + channel (K v 7.1), and ryanodine receptor (RyR2) ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ). Modulation is achieved either via direct binding or through the regulatory multifunctional Ca 2+ /CaM-dependent kinase (CaMKII) with the γ (CaMKIIγ) and δ (CaMKIIδ) isoforms present in heart ( 46 , 47 , 48 , 49 ).…”
mentioning
confidence: 99%
“…The HVCN1 knockout hearts exhibited differential expression of cardiac ion channels, including upregulated L-type calcium channel, I Kur , HCN2, and downregulated SERCA pump. These results indicated that HVCN1 was associated with the electrophysiological remodeling in cardiomyocytes, and HVCN1 might regulate cardiac ion channels function like other channel partners ( Hong et al, 2020 ; Wu and Hong, 2021 ). Previous studies reported that deficits of the HVCN1 channel by the gene deletion or pharmacological block produced intracellular acidification (low pH i ) in a variety of cell types ( Cherny and DeCoursey, 1999 ; Wu et al, 2012 ; Asuaje et al, 2017 ).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, calmodulin, a small protein acting as a signal transducer that regulates neuronal plasticity, muscle contraction, and immune response [ 86 ], modulates the voltage-gated sodium-channel gating process, alters the sodium current density, and regulates the trafficking and expression of sodium channel proteins. Many mutations in the calmodulin-binding IQ domain give rise to diseases, including epilepsy [ 23 ].…”
Section: Involvement Of Ion Channels and The Immune System In Epilept...mentioning
confidence: 99%
“…The role of ion channels in epilepsy and epileptogenesis is an active focus of current research, and the alteration of the ion channels involved in epileptogenesis has been established in numerous studies [ 17 , 18 , 19 , 20 , 21 ]. It has been further suggested that some ion channels are associated with altered immunological/inflammatory responses involved in the generation of epilepsy [ 22 , 23 ] and in immune-mediated epilepsy.…”
Section: Introductionmentioning
confidence: 99%